2010
DOI: 10.1021/ie100607u
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Oxidation of Nitric Oxide (NO) by Aqueous Solutions of Sodium Persulfate in a Bubble Column Reactor

Abstract: The absorption-oxidation of nitric oxide (NO) by aqueous solution of sodium persulfate (Na 2 S 2 O 8 ) has been studied in a bubble column reactor operated in semibatch mode. The effects of different process variables such as the persulfate concentration (0.01-0.2 M), temperature (23-90°C), pH (4-12), sodium chloride concentration (0-0.5 M), and NO concentration (500-1000 ppm) were studied. In general, the NO fractional conversion (percent of inlet NO removed) at all temperatures increased almost linearly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 40 publications
10
141
2
Order By: Relevance
“…It is noted that the redox potentials of the Cl À containing radicals are much lower than 2.6 V of sulfate radicals [14]. Furthermore, the generated Cl ÀÅ 2 and Cl Å could further react with itself to form Cl 2 and Cl À [31,32]. CO 2À 3 and HCO À 3 are the good scavengers for hydroxyl radicals, similar findings were reported everywhere [33].…”
Section: Effect Of Coexisting Inorganic Anionssupporting
confidence: 78%
“…It is noted that the redox potentials of the Cl À containing radicals are much lower than 2.6 V of sulfate radicals [14]. Furthermore, the generated Cl ÀÅ 2 and Cl Å could further react with itself to form Cl 2 and Cl À [31,32]. CO 2À 3 and HCO À 3 are the good scavengers for hydroxyl radicals, similar findings were reported everywhere [33].…”
Section: Effect Of Coexisting Inorganic Anionssupporting
confidence: 78%
“…For instance, on the persulfate oxidation of TCE at pH 7 and 20°C, Liang et al [45] demonstrated that TCE degradation in the presence of chlorides revealed no effect on the degradation rate especially at chloride levels below 0.2 M, but at chloride levels greater than 0.2 M, TCE degradation rate reduced with an increase of the chloride ion concentration. However, Khan and Adewuyi [46] reported that the absorption and oxidation of nitric oxide (NO) significantly improved with the addition of NaCl in sodium persulfate solutions. In addition, in our previous study of 1,1,1-trichloroethane oxidation stimulated by thermally activated persulfate [47], we found anions Cl À and HCO 3 À had negative effects on TCA removal over the range of 1 to 100 mM.…”
Section: Influences Of Solution Matrix On the Degradation Of Tce In Pmentioning
confidence: 98%
“…Therefore, alternative cost-effective and environmentally friendlier processes such as using wet scrubbing agents, capable of significantly increasing the solubility of NO in water, are of ardent interest. [3][4][5][6][7] As a result, the uses of aqueous solutions of H 2 O 2 , NaClO 2 , KMnO 4 , iron and cobalt chelated compounds, and sonochemical oxidation processes for NO removal, are the subjects of a number of recent studies. [8][9][10][11][12][13][14][15] In 2010, Khan and Adewuyi reported, for the first time, the use of aqueous sodium persulfate (Na 2 S 2 O 8 ) activated by temperature for NO removal, and commented on its safety, stability and environmental benign nature.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal and Fe 2+ ion activation of the persulfate anion leads to the production of the sulfate radicals (SO 4 •− ), which is responsible for the production of OH • that acts as the main oxidant for the conversion of NO in the aqueous solution. [5,6,[21][22][23] The following major pathways have been proposed: Finally, the respective concentration values were multiplied by their respective dilution factors, and then averaged to determine the concentration of a particular sample. The concentration profiles of the species were then obtained.…”
Section: Introductionmentioning
confidence: 99%